ArabOnto: experimenting a new distributional approach for building Arabic ontological resources. (2nd May 2012) - Bounhas, Ibrahim; Elayeb, Bilel; Evrard, Fabrice; Slimani, Yahya
Ontologies are useful for modelling and retrieving knowledge in complex information systems. Ontology construction environments use statistical and linguistic information to extract knowledge from corpora. Within the great improvement in this field, there is a need to introduce the Arabic language in these environments. We present the ArabOnto architecture modelling the process of Arabic ontology extraction from corpora. ArabOnto focuses on linguistic issues related to Arabic term extraction and linking (i.e. from morphosyntactic parsing to clustering). We experiment our system by testing several alternatives on three domains. Besides, our ontologies are validated in the context of an information retrieval system.